Special Economic Zones in India: Some Ground Realities - Singh, Mandeep; Khurana, Ashok (Prabandhan: Indian Journal of Management, 2010)
India is pioneer country in Asia to recognize the effectiveness of the Export Processing Zone (EPZ) model in promoting exports, with Asia's first EPZ set up in Kandla in 1965. With a view to prevail over the shortcomings practiced on account of the multiplicity of controls and clearances; deficiency of world-class infrastructure, and a wobbly fiscal regime and with a view to magnetize larger foreign investments in India, the Special Economic Zones (SEZs) Policy was announced in April 2000. This policy projected to make SEZs an engine for economic growth supported by excellent infrastructure complemented by an attractive fiscal package, both at the Centre and the State level, with the minimum possible regulations. SEZs in India functioned from 1.11.2000 to 09.02.2006 under the provisions of the Foreign Trade Policy and fiscal incentives were made effective through the provisions of relevant statutes. After extensive consultations, the SEZ Act, 2005, supported by SEZ Rules, came into effect on 10th February, 2006, This paper analyses the economics of SEZs in India. To commence with, the development of the SEZ Policy in India is discussed. Secondly, it attempts to examine the current status of SEZs in shaping of employment generation, attracting investment, and exports promotion. The paper also elaborates the incentive packages and infrastructure facilities offered by the zones in India. Last but not least, the paper discusses a few fiery issues, and gives recommendations to augment the efficacy of SEZs in India.